Consideratii genetice despre categoria prepositiei în limbile romanice, cu referire mai detaliata la limba romanâ - Rusiewicz-Woźny, Krystyna (Studia Romanica Posnaniensia, 2001)
There is a strong connection between the occurrence of prepositions and the reduction of the number of cases. Prepositions and casual flexions have a common objective to assure the placement of a noun in a text conform to syntactic rules. The formation of prepositions can be perceived as a replacement of internal morphology with external morphology.